Ultrasonographic evaluation of contralateral exploration of patent processus vaginalis in unilateral inguinal hernia (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 192-6. The abstract of this article is available on the PubMed website